FACTOR THAT AFFECT THE VALUE OF THE COMPANY IN THE FOOD AND BEVERAGE SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2017-2019 - Rika Fitri Yani; Kasmadi Kasmadi; Muhammad Salis (STIE Bangkinang Publishing, 2020)
Research to determine the influence of factors consisting of stock liquidity, solvency, provitability and dividends simultaneously and partially on the value of the company in food and beverage companies listed on the Indonesian Stock Exchange 2017-2019. Sampling is done purposive sampling method as many is 30 companies in food and beverage company listed on the Indonesian Stock Exchange 2017-2019. Data analysis was performed using multiple linear regression models. Based on the simultaneous test results, Stock Trading Frequency (STF), Debt to Equity Ratio (DER), Return On Assets (ROA) and Divident Payout Ratio (DPR) to have an affect significant on the Price to Book Value, which means that stock liquidity, solvency, provitability and dividends to have an affect with together on the value of the company in food and beverage companies listed on the Indonesian Stock Exchange 2017-2019. While based on the partially test results, Stock Trading Frequency (STF), Debt to Equity Ratio (DER), Return On Assets (ROA) and Divident Payout Ratio (DPR) to have an affect significant on the Price to Book Value (PBV), which means that stock liquidity, solvency, provitability and dividends to have an affect with individual on the value of the company in food and beverage companies listed on the Indonesian Stock Exchange 2017-2019. The closeness of the relationship that occurs between the atractiveness stock liquidity, solvency, provitability and dividends on the value of the company is very strong with a correlation coefficient (R) of 86,0%. While contribution of independent variables to the dependent variables is equual to 72,9%.